2012
DOI: 10.4103/0971-6580.94512
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of chromium-vi by chromium resistant lactobacilli: A prospective bacterium for bioremediation

Abstract: Chromium is a toxic heavy metal, which primarily exists in two inorganic forms, Cr (VI) and Cr (III). Highly soluble hexavalent chromium is carcinogenic due to its oxidizing nature. It is well established that the intestinal bacteria including Lactobacilli have regulatory effect on intestinal homeostasis and a breakdown in the relationship between intestinal cells and bacteria results in the manifestation of gastrointestinal (GI) disorders. In this study Cr (VI) resistance was developed in Lactobacillus strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Some lactobacilli are Cr-resistant and would be useful for Cr detoxification and bioremediation, e.g. L. paracase CL1107 manifested in vitro Cr(VI) reduction ability, though not as competent as TW1-1 23 , 24 . TW1-1 reduced tissue absorption of Cr by promoting its excretion through feces, implying that TW1-1 might exert its effects in two possible ways.…”
Section: Discussionmentioning
confidence: 99%
“…Some lactobacilli are Cr-resistant and would be useful for Cr detoxification and bioremediation, e.g. L. paracase CL1107 manifested in vitro Cr(VI) reduction ability, though not as competent as TW1-1 23 , 24 . TW1-1 reduced tissue absorption of Cr by promoting its excretion through feces, implying that TW1-1 might exert its effects in two possible ways.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the diverse applications of chromium and its drastic impacts on humans and environment, there is an urgent need to design strategies to remove Cr(VI) from effluents. Recently, a number of bacterial strains have been isolated with the ability to reduce the highly toxic Cr(VI) to the less toxic Cr(III) (Mishra et al, 2012;Long et al, 2013;Voica et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These observations are in corroboration with Mishra et al . [ 33 ] wherein it is reported that the Cr-resistant probiotic LAB strains showed similar biochemical parameters as their respective normal strain.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, both were tested for antibiotic sensitivity by standard disc diffusion method[ 33 ] against Kanamycin (30µg), Norfloxacin (10 µg), gentamycin (10 µg), chloramphenicol (30 µg), amoxycillin (10 µg), ciprofloxacin (5 µg), and teicoplanin (30 µg). The antibiotic discs were procured from HiMedia.…”
Section: Methodsmentioning
confidence: 99%